PENGEMBANGAN E-LEARNING GUNA MENDUKUNG PELAKSANAAN DIKLAT DI BALAI PENDIDIKAN DAN PELATIHAN KEAGAMAAN DENPASAR - Sudarsana, Komang (Jurnal Visi Ilmu Pendidikan, 2020)
This research aims to produce learning in the form of e-learning as a blended learning that is valid, practical, and effective in the execution of training preparation of learning materials in Balai Diklat Keagamaan Denpasar. This development research is based on the lack of a variety of media and learning materials that are used in the training process, the learning methods applied are still conventional, and the limited communication between lecturer with participants. The development procedure uses the ADDIE model consists of five stages: (1) analysis, (2) design, (3), development, (4) implementation, and (5) evaluation. The results showed that the teaching materials developed have met the aspects of validity, practicality, and effectiveness. The results of the validity test shows that e-learning as a blended learning is at a very good category based on test experts. E-learning also has fulfilled the practical aspect seen from the participants's response related to ease of use and interface attractiveness. The t-test results show that there is a significant difference between the mean score of learning outcomes before and after using e-learning as blended learning. Where the posttest average value is greater than the average value of pretest and has met the minimum predefined criteria that have been set. Based on this, e-learning as a blended learning is considered effective in improving learning outcomes.